Meeting report: FDA public meeting on patient‐focused drug development and medication adherence in solid organ transplant patients. Issue 3 (25th January 2018) - Ettenger, Robert; Albrecht, Renata; Alloway, Rita; Belen, Ozlem; Cavaillé‐Coll, Marc W.; Chisholm‐Burns, Marie A.; Dew, Mary Amanda; Fitzsimmons, William E.; Nickerson, Peter; Thompson, Graham; Vaidya, Pujita
Abstract : The Food and Drug Administration (FDA) held a public meeting and scientific workshop in September 2016 to obtain perspectives from solid organ transplant recipients, family caregivers, and other patient representatives. The morning sessions focused on the impact of organ transplantation on patients' daily lives and the spectrum of activities undertaken to maintain grafts. Participants described the physical, emotional, and social impacts of their transplant on daily life. They also discussed their posttransplant treatment regimens, including the most burdensome side effects and their hopes for future treatment. The afternoon scientific session consisted of presentations on prevalence and risk factors for medication nonadherence after transplantation in adults and children, and interventions to manage it. As new modalities of Immunosuppressive Drug Therapy are being developed, the patient perceptions and input must play larger roles if organ transplantation is to be truly successful. Abstract : The authors summarize a FDA public meeting considering the benefits and challenges of immunosuppressive therapy and how medications impact recipients' lives, the challenges of medication adherence, and future considerations that can guide the FDA in approving future immunosuppressive therapy.